Cu(ii) complexes of a tridentate N, N, O-donor Schiff base of pyridoxal: synthesis, X-ray structures, DNA-binding properties and catecholase activity. (11th May 2018) - Mondal, Satyajit; Chakraborty, Moumita; Mondal, Antu; Pakhira, Bholanath; Blake, Alexander J.; Sinn, Ekkehard; Chattopadhyay, Shyamal Kumar
Abstract : DNA binding and catecholase activities of two Cu(ii ) complexes [Cu(L1 )X] (X = N3, NCS) of pyridoxal derived ligands are reported. Abstract : Two new Cu(ii ) complexes [Cu(L1 )(N3 )] (1 ) and [Cu(L1 )(NCS)] n (2 ), where HL1 (( E )-4-((2(dimethylamino)ethylimino)methyl)-5-(hydroxymethyl)-2-methylpyridin-3-ol) is an N, N, O-donor Schiff base ligand, have been synthesized. These complexes were characterized on the basis of their spectroscopic, electrochemical, and other physicochemical properties. X-ray crystal structure determination reveals that in complex1, Cu(ii ) is in a square planar geometry with the N, N, O-donor ligand and a terminally coordinated azide ion. In complex2, however, Cu(ii ) has a square pyramidal geometry, and apart from the tridentate Schiff base ligand there is a thiocyanate ion, which acts in a μ1, 3 -bridging mode, connecting the adjacent Cu(ii ) atoms in an axial–equatorial fashion forming a one dimensional chain. Cyclic voltammetry shows that the complexes undergo Cu(ii )/Cu(i ) reductions at −0.40 to −0.55 V followed by imine reduction at around −0.7 V. Cu(i )/Cu(0) reduction is observed at approximately −0.9 V. Complex1 also shows appreciable catalytic activity for the aerial oxidation of 3, 5 DTBCH2 to DTBQ (catecholase activity). Both the complexes also show strong binding affinity towards calf-thymus DNA.